Consideration of Sex Differences in Design and Reporting of Experimental Arterial Pathology Studies—Statement From ATVB Council. Issue 2 (February 2018) - Robinet, Peggy; Milewicz, Dianna M.; Cassis, Lisa A.; Leeper, Nicholas J.; Lu, Hong S.; Smith, Jonathan D.
Abstract : There are many differences in arterial diseases between men and women, including prevalence, clinical manifestations, treatments, and prognosis. The new policy of the National Institutes of Health, which requires the inclusion of sex as a biological variable for preclinical studies, aims to foster new mechanistic insights and to enhance our understanding of sex differences in human diseases. The purpose of this statement is to suggest guidelines for designing and reporting sex as a biological variable in animal models of atherosclerosis, thoracic and abdominal aortic aneurysms, and peripheral arterial disease. We briefly review sex differences of these human diseases and their animal models, followed by suggestions on experimental design and reporting of animal studies for these vascular pathologies.